2009
DOI: 10.1136/adc.2008.145144
|View full text |Cite
|
Sign up to set email alerts
|

Rice: a common and severe cause of food protein-induced enterocolitis syndrome

Abstract: This study highlights the emerging importance of rice, a food commonly thought to be "hypoallergenic", as a significant trigger of FPIES. Paediatricians should be aware that rice not only has the potential to cause FPIES, but that such reactions tend be more severe than those caused by cow's milk/soy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 17 publications
1
54
1
3
Order By: Relevance
“…[5][6][7][8] El arroz es el alimento sólido que produce SEIPA con mayor frecuencia; además, se asocia a reacciones más graves que otros alimentos. 9 El diagnóstico se basa en la historia clínica, sospecha de alimento causal, exclusión de otras posibles etiologías y, en algunos casos, es necesaria una prueba de provocación oral para confirmar la sospecha diagnóstica, aunque se considera una prueba de riesgo 10 que debe realizarse en el ámbito hospitalario. En nuestro caso, los padres relacionaron, en el segundo episodio, el cambio de marca de leche con el inicio de los síntomas, pero, tras comprobar la tolerancia de leche durante el ingreso, se decidió realizar una prueba de provocación que confirmara la sospecha.…”
Section: Discussionunclassified
“…[5][6][7][8] El arroz es el alimento sólido que produce SEIPA con mayor frecuencia; además, se asocia a reacciones más graves que otros alimentos. 9 El diagnóstico se basa en la historia clínica, sospecha de alimento causal, exclusión de otras posibles etiologías y, en algunos casos, es necesaria una prueba de provocación oral para confirmar la sospecha diagnóstica, aunque se considera una prueba de riesgo 10 que debe realizarse en el ámbito hospitalario. En nuestro caso, los padres relacionaron, en el segundo episodio, el cambio de marca de leche con el inicio de los síntomas, pero, tras comprobar la tolerancia de leche durante el ingreso, se decidió realizar una prueba de provocación que confirmara la sospecha.…”
Section: Discussionunclassified
“…[1][2][3][4] Ancak yine olgularımızda olduğu gibi, pirinç ve yulaf gibi hipoallerjenik olarak bilinen besinlerle de olayın tetiklendiği gözlenmiş-tir. 8,11,12 İlk olgumuzda yulaf ezmesinden sonra üçüncü kez semptomların ortaya çıkışı gözlenmiş-ken, ikinci olgumuzda ilk semptomların ortaya çı-kışında sorumlu tutulabilecek besin pirinçtir. Ayrıca literatürde meyve proteinleri (elma, muz vb.)…”
Section: -41012unclassified
“…9 Ancak patates, tavuk, yulaf, pirinç ve balık gibi hipoallerjenik olarak bilinen besinler ile de hastalı-ğın tetiklendiği gözlenmiştir. [1][2][3][4]8,[10][11][12] Nadir görülmekle beraber hayatı tehdit edici bir hastalık tablosu olması dolayısıyla BPİES'in tanı ve tedavisinin, allerji hekimleri kadar çocuk hekimleri tarafından da yapılabilmesi zorunludur. İki farklı olgumuzu tanı ve tedavideki yaklaşımlarımızı tartışmak ve bu hastalık tablosu konusunda bilgilenmeyi artırmak için sunmayı uygun bulduk.…”
unclassified
“…Moreover, Yamada et al (1985) reported that rice has apparently exceeded other cereals in allergenicity, and ranked second after egg whites as the most common potential allergy-causing food, as assessed by an IgE RAST. A recent report (Mehr et al, 2009) noted that rice was a common trigger of a severe type of allergic reaction called food proteininduced enterocolitis syndrome (FPIES) in children.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Yamada et al (1985) reported that rice has apparently exceeded other cereals in allergenicity, and ranked second after egg whites as the most common potential allergy-causing food, as assessed by an IgE RAST. A recent report (Mehr et al, 2009) noted that rice was a common trigger of a severe type of allergic reaction called food proteininduced enterocolitis syndrome (FPIES) in children.Several rice proteins with molecular masses of 14-16, 26, 33 and 60 kDa were demonstrated to be recognized by serum IgE of patients showing hypersensitive reactions to rice ingestion (Urisu et al, 1991;Usui et al, 2001). The first reported allergen in rice was a 16 kDa protein with reactivity for IgE of rice-hypersensitive patients (Matsuda et al, 1991).…”
mentioning
confidence: 99%